Incidence of hepatitis B and C in children with cancer: a single institution experience in Iraq (Texas Journal of Medical Science, 2022)
Hepatitis viruses, including B and C, are present in a large number of cancer cases, such as leukemia, and they are responsible for most of hepatitis. Objective: To determine the incidence of hepatitis virus infection among children being treated for cancer and to evaluate the factors that may increase the risk of infection. Methods: A cross-sectional study was conducted at Al-Imam Al-Hussain Oncology Center in Kerbala during a period of seven months, from the 13th of June 2019 till the 13th of January 2020. One hundred fifty-one patients were included in this study; their ages were < 18 years. They were diagnosed with cancer for at least six months before. They were either on current treatment or finished treatment and were attending for follow-up. A two ml of blood was drawn from all patients to test for liver function test, hepatitis B surface antigen (HBs Ag), and anti-hepatitis C antibody (anti-HCV). Results: In this study, the incidence of hepatitis C was 4%, and the incidence of hepatitis B was 1.3%. The highest prevalence of hepatitis infection was significantly seen in patients who received platelets transfusion more than ten times, in leukemia patients, in patients who received packed RBC transfusion 1-10 times, in patients who had elevated liver function tests, and in patients who received the last transfusion outside Kerbala. Conclusion: Incidence of blood born hepatitis is comparable with other published studies, higher with more frequent blood product transfusion, and higher with hematological malignancies rather than solid malignancies